Learning to Be a Father: How is it done? Isn't there a manual somewhere? - Kate Fogarty; Garret D. Evans (EDIS)
Revised! FCS2138, a 5-page fact sheet by Kate Fogarty and Garret D. Evans, discusses ways men can learn how to be good fathers. Includes recommended resources in English and Spanish, and references. Published by the UF Department of Family Youth and Community Sciences, November 2009.